1972
DOI: 10.1111/j.1529-8817.1972.tb04030.x
|View full text |Cite
|
Sign up to set email alerts
|

THE BIOCHEMICAL ANALYSIS OF SOME ESTUARINE PHYTOPLANKTON SPECIES. I. FATTY ACID COMPOSITION12

Abstract: SUMMARY The fatty acid composition of 10 species of estuarine phytoplankton was determined using gas‐liquid chromatography. Nine of the species were isolated from Yaquina Bay, Oregon. These species were common components of the phytoplankton of the bay. The tenth species, Isochrysis galbana, was obtained from the Culture Collection of Algae at Indiana University. The 10 organisms comprised 3 species of Chlorophyta, 1 species of Cryptophyta, and 6 species of Chrysophyta. Twenty‐eight fatty acids were found in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

1974
1974
1995
1995

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 20 publications
3
9
0
Order By: Relevance
“…The 14:0 and 16:1 FFA in diatoms, S. costatum and C. didymum, obtained in this study were particularly abundant compared with fatty acids of raphidophyte flagellates. The high proportions of 14:0, 16:0, 16:1, and 20:5 acids and low percentages of Cl8 FFA series in both diatoms under investigation are in agreement with previous analyses for the total lipids of diatoms (12)(13)(14)(15)(16)(17). It has been shown that some minor fatty acids in phytoplankton are derived from bacteria (14,15), and in this connection, Kattner et al (16) suggested that C18 acids are not synthesized by S. costatum.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…The 14:0 and 16:1 FFA in diatoms, S. costatum and C. didymum, obtained in this study were particularly abundant compared with fatty acids of raphidophyte flagellates. The high proportions of 14:0, 16:0, 16:1, and 20:5 acids and low percentages of Cl8 FFA series in both diatoms under investigation are in agreement with previous analyses for the total lipids of diatoms (12)(13)(14)(15)(16)(17). It has been shown that some minor fatty acids in phytoplankton are derived from bacteria (14,15), and in this connection, Kattner et al (16) suggested that C18 acids are not synthesized by S. costatum.…”
Section: Resultssupporting
confidence: 92%
“…An unidentified peak also was eluted in the HPLC of S. costatum fatty acids, but with a difference in RRT (0.47). From the RRT, the unknown peaks are estimated to those of the 16:4 and 16:3 frequently observed in phytoplankton (12)(13)(14)(15)(16)(17) because the ADAM derivatives of FFA elute in the order of increasing carbon number and decreasing number of double bonds in reversed-phase HPLC (11). Linearity of the respective peak area with increasing concentrations of FFA was confirmed over a wide range of concentrations, showing that reaction of ADAM with each FFA was both quantitative and reproducible (11 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…T h e fatty acid composition of CyclotelEa rneneghiniana is similar to reports of fatty acid composition for other diatoms (Kates and Volcani 1966, DeMort et al 1972, Orcutt and Patterson 1975, Ben-Amotz et al 1985). In addition to the major fatty acids, we found two branched fatty acids (iso-l3:O and iso-14:O) consistently present but in very low quantities.…”
Section: Discussionsupporting
confidence: 82%